PENYULUHAN DALAM RANGKA PEMBERDAYAAN MASYARAKAT DALAM PERUBAHAN PERILAKU BUANG AIR BESAR SEMBARANGAN DI KELURAHAN SEGALA MIDER - Sarip Usman; Bambang Murwanto (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Diarrhea is still an important health problem, because it contributes to around 4,800 deaths of children under five worldwide. With an incidence of 11%, diarrhea is the second cause of death in children under five in Indonesia. Prevention and control of diarrhea mainly through the intervention of drinking water and healthy latrines. Community service aims to change the behavior of open defecation, with four stages: building understanding, common perception, counseling, and assisting target households. At the end of the stage, an evaluation is carried out to assess success, obstacles, and follow-up plans. The concept of "sharing roles" was also developed for all service partners. Community service activities resulted in 16 healthy latrines, which were accessed by 21 households. This result indicates that all households in the Mider Kelurahan have access to healthy latrines. The application of the concept of "sharing roles" is able to produce outputs according to the target, form a mutual cooperation work system for beneficiaries, and improve values. A joint commitment is needed in carrying out community empowerment, and the involvement of other parties broadly.